Optimization of AVR in Micro-hydro Power Plant Using Differential Evolution (DE) Method - Firmansyah, Rio; Ali, Machrus; Ajiatmo, Dwi; Raikhani, Agus; Siswanto, Makhaban (Universitas Negeri Malang, 2020)
Micro-hydro Power Plant had three primary components: water (as the energy resource), turbine, and generator. Water that flew in a specific capacity was channeled from a certain height to the installation house (turbine house). In the powerhouse, the water installation pounded the turbine that made the turbine received direct energy from the water and turn it into mechanical energy and caused the turbine shaft to spin. Changes in the loading could cause fluctuation in the systemâ€™s frequency and voltage. This problem could damage electrical equipment. Therefore, the Automatic Voltage Regulator (AVR) was used to control and stabilize the voltage. This research used PID controller to obtain the optimized control parameter in the Micro-hydro Power Plant. This research compared the simulations of without control method, with PID-ZN control method, and with PID-DE method to obtain the best control method. The comparison simulations showed that the best response in the micro-hydro plant and the AVR system was from the PID-DE controller. These results might be a reference for future research with other methods that might generate better results. Â Â